2018
DOI: 10.1167/tvst.7.6.33
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Gonioscopic and EyeCam Assessments of Angle Dimensions Using Anterior Segment Optical Coherence Tomography

Abstract: PurposeTo evaluate the relationship between angle dimensions assessed by gonioscopy or EyeCam and anterior segment optical coherence tomography (AS-OCT).MethodsSubjects aged 50 years or older were recruited from the Chinese American Eye Study (CHES). Each subject underwent a complete ocular exam, including gonioscopy, AS-OCT, and EyeCam. Angle closure was defined as three or more quadrants in which pigmented trabecular meshwork could not be visualized. Angle opening distance (AOD), angle recess area (ARA), tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Similarly, the scleral spur (grade 3) was also indistinguishable from both posterior trabecular meshwork (grade 2) and ciliary body (grade 4). Similar to the work of Xu et al, 15 we also found a wider distribution of quantitative values for grades 3 and 4, supporting the notion that the measurement ceiling is not well-defined. This was demonstrated in both evaluation of the distributions of quantitative values and the results of the clustering algorithm identifying a distinct subset of angles with very large quantitative values.…”
Section: Inequalities Contribute To Discordance Between Gonioscopic Gsupporting
confidence: 91%
“…Similarly, the scleral spur (grade 3) was also indistinguishable from both posterior trabecular meshwork (grade 2) and ciliary body (grade 4). Similar to the work of Xu et al, 15 we also found a wider distribution of quantitative values for grades 3 and 4, supporting the notion that the measurement ceiling is not well-defined. This was demonstrated in both evaluation of the distributions of quantitative values and the results of the clustering algorithm identifying a distinct subset of angles with very large quantitative values.…”
Section: Inequalities Contribute To Discordance Between Gonioscopic Gsupporting
confidence: 91%
“…30 This finding may be related to the fact gonioscopy grades are only weakly associated with angle width in eyes with angle closure. 31 Conversely, quantitative AS-OCT measurements of angle width have a strong association with intraocular pressure, a strong risk factor for glaucomatous optic neuropathy, in a subset of eyes with primary angle closure disease. 32 However, the clinical utility of this finding is currently limited by the technical challenges associated with manual analysis of AS-OCT images.…”
Section: Discussionmentioning
confidence: 99%
“…Gonioscopy, performed in a dark room (with and without indentation), was performed on all participants by a single examiner (ZHY), who was masked to the UBM findings, using a Goldmann two-mirror lens (Ocular Instruments Inc., Bellevue, WA, USA). The angle in each quadrant was graded based on the observed anatomical structures, following the modified Shaffer grading system [ 8 , 9 ] (grade 0, no structure or Schwalbe's line observed; grade 1, visible anterior nonpigmented trabecular meshwork; grade 2, visible posterior pigmented trabecular meshwork; grade 3, visible scleral spur; grade 4, visible ciliary body). Angle quadrants were considered closed if they were grade 0 or 1.…”
Section: Methodsmentioning
confidence: 99%